The (in)visibility of translation and translators in the Swedish publication of post-Soviet Russian literature: An analysis of peritexts - Podlevskikh Carlström Malin (Slovenia, 2022)
In this article the (in)visibility of translation and translators in Sweden is studied, based on the
analysis of a corpus of 82 post-Soviet Russian novels. The aim is to investigate how (if at all) the
peritexts reveal the foreign nature of the text and the identity of the translator. The analysis shows
that the translator is rather invisible in the external peritext, which is placed on the cover or dust
jacket of the published translation, while the foreign (and consequently also the translated) nature
of the novel is highlighted. The translator’s visibility inside Swedish translations of post-Soviet novels
is usually signaled on the title page. Apart from this, the translator is invisible. A few translator’s
comments and notes are included in the translation, but usually these are inconspicuous and not
explicitly attributed to the translator. Moreover, they are written in an apologetic tone and do not
seem to wish to disturb the reader.